Cykl życia organizacji - Smela, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Organizational life cycle is a concept that divides time of organization's duration into particular stages: rise, growth, maturity and declining time. During each stage an organization pursues different goals, has different structure, managing style and different system of taking decision. There are also a few types of crisis that a growing organization should overcome and chances that should be used. Organizational life cycle is also connected with product life cycle and combination of these two ideas helps to manage a company. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 394-405